Analisis Variasi Nilai Temperatur Material VCN150 Untuk Crusher Pencacah Plastik Dengan Proses Heat Treatment - Ariyanto, Aariyanto; Yudo, Eko; Nicola, Adyu (Manutech : Jurnal Teknologi Manufaktur, 2025)
Steel is one of the most widely used types of metal in the engineering field. There are many types of steel materials with different properties and characteristics, and steel materials can be used depending on their purpose. Steel contains various alloying elements. Although carbon is the element that has the greatest influence on the properties of steel, other elements cannot be ignored. The carbon content affects the mechanical properties of steel, such as hardness, ductility, formability, and other mechanical properties. This study aims to evaluate whether VCN 150 alloy steel can be used as an alternative material for cutting blades in plastic shredding machines based on its hardness value. The heat treatment process is conducted using varying temperatures of 800°C, 840°C, and 880°C, as well as using different cooling media, namely oil, seawater, and saltwater (25% salt content), then followed by a tempering process at temperatures of 100°C and 150°C. The research results indicate that the cooling medium significantly affects the hardness value of the material. A combination of a temperature of 800 °C and seawater cooling produces the maximum hardness value. The increase in hardness value becomes an alternative potential for plastic cutting blades.